Pharmacokinetics and brain tissue distribution of Gastrodia elata extract in normal and cerebral ischemic rats: a comparative study - Ji Shao; Qi Xu; Yunyun Luo; Ting Dong; Xue Han; Bilian Chen; Huazhong Ying; Cuifen Fang; Qiaojuan Shi (Frontiers in Pharmacology, 2025)
ObjectiveThis study systematically investigated the pharmacokinetic characteristics, cerebral distribution, and metabolic transformation of Gastrodia elata components in both healthy and cerebral ischemia rat models.MethodsChemical profiling of Gastrodia elata was conducted using UPLC-Q-TOF-MS. Based on the systemically absorbed constituents identified in plasma and brain tissues of dosed rats, a validated UPLC-QQQ-MS method was established to quantitatively determine target compound levels in plasma and brain tissues of both normal and cerebral ischemic rats following 3-day oral administration. Subsequently, UPLC-Q-TOF-MS was reapplied to conduct identification and comparative analysis of xenobiotic metabolites in both in vivo systems and brain tissues.ResultsBased on the established therapeutic efficacy of Gastrodia elata extract against cerebral ischemia-reperfusion injury, chemical profiling identified 53 constituents, among which six were simultaneously detected in plasma and brain tissue of dosed rats. The established simultaneous quantitative analytical method demonstrated reduced gastrointestinal absorption of parishin A, parishin B, parishin C, parishin E and gastrodin in ischemic model rats compared to healthy controls. Notably, brain accumulation of these compounds was significantly increased in ischemic models, attributable to compromised blood-brain barrier integrity. Xenobiotic metabolite analysis identified nine biotransformation products, four of which exhibited quantifiable exposure levels in brain tissues across all experimental groups.ConclusionThis study systematically revealed the bioactive components of Gastrodia elata and their cerebral distribution patterns. The pharmacokinetic characteristics of gastrodin and related bioactive compounds were also elucidated. These findings provide a valuable reference for pharmacological exploration, safety evaluation, and clinical application of Gastrodia elata in cerebrovascular disorders.